Optimal Location of a Distributed Generator for Power Losses Improvement. (2016) - Dulău, Lucian Ioan; Abrudean, Mihail; Bică, Dorin
Abstract: This paper describes the optimal location of a 2.3 MW distributed generator (DG) in a test system (IEEE 14 bus test system) based on the power losses. The distributed generator (DG) optimal location will determined considering the power losses at each bus where the DG is connected. The power losses at each bus will be determined with the Neplan software, using the Newton-Raphson extended method.